Lote Bravo: memory, mourning, and vulnerability in the work of Teresa Margolles - Geraldo, Sheila Cabo; Souza, Karenn de Amorim e (Farol, 2025)
This article analyzes the installation Lote Bravo (2005), by the Mexican artist Teresa Margolles, created in response to femicides in Ciudad Juárez. The aim is to understand how the artist transforms the materiality of death into a sensitive-political device of memory. The work displaces historically invisible bodies into the space of the common, challenging the naturalization of gender violence. The approach is based on the work of Judith Butler, María Lugones, and Jacques Rancière, and relates concepts such as precariousness, gender coloniality, and the sharing of the sensible. Lote Bravo reconfigures the visibility of precarious lives, converting mourning into a political gesture. Thus, it can be concluded that Margolles’ work proposes an aesthetics of memory that challenges the normalization of violence against women in northern Mexico.